The Role of Participative Leadership on Job Performance: Job Satisfaction as an Intervening Variable - Dewi, Santi Riana; Nafiuddin; Sunaryo, Deni (Ilomata International Journal of Management, 2025)
This study aims to examine the effect of participative leadership style on employee performance, with job satisfaction as a mediator. The results of the study aids in describing how performance and participative leadership are related, with job satisfaction as an intervening variable, particularly in the manufacturing industry. The study employed a quantitative method, with 99 employees of a pesticide company in Banten province as respondents. Samples were populated based on a purposive sampling technique. Structural equation modeling (SEM) techniques were employed for the analysis, utilizing SmartPLS 4. The results of the study show that participative leadership has a significant direct effect on employee performance (M=0.623; P=0.000). Job satisfaction also has a significant direct effect on performance (M=0.651; P=0.000). In addition, job satisfaction mediates between participative leadership and performance (M=0.464; P=0.000). In addition, participative leadership style and job satisfaction explain 58.8% (R2=0.588) of the performance. Hence, the companies should focus on training all leaders to practice participative leadership in daily work and continuously improving factors that improve employee job satisfaction. Both of the focuses will improve employee performance.